The impact of hospitalization on the performance of capsule endoscopy (CE). Issue 6 (June 2017) - Albrecht, Heinz; Vetter, Marcel; Dauth, Wolfgang; Zoicas, Flavius; Neurath, Markus Friedrich; Hagel, Alexander Fritzkarl
Abstract: Background: For proper evaluation of capsule endoscopy (CE), a complete examination is necessary. Aim: We evaluated risk factors of an incomplete CE with focus on patient hospitalization. Methods: We retrospectively evaluated 161 consecutive patients who underwent CE between 01.07.2013 and 13.03.2016. Main indications were active bleeding, iron deficiency anemia (IDA), inflammatory bowel disease (IBD), abdominal pain, and familial adenomatous polyposis (FAP). Results: We report the results of 103 in-patients and 56 out-patients. Eighty-two patients were male, average age was 58.9 years (range 18–90). Indications for CE were active bleeding (103 patients), IDA and IBD (16 patients), and FAP, abdominal pain and others (eight examinations each). All FAP patients were out-patients, but showed the longest small bowel transit time (SBTT) of 443.6 min (p = 0.0001). The shortest SBTT was found in out-patients without FAP (267.5 min, p < 0.05). In the in-patient group, nine endoscopies did not record the entire small bowel (8.7%) due to battery depletion, compared with only one incomplete examination in the out-patients (1.8%, p = 0.036). We found pathologic lesions in the last 30 min of the SBTT in 43 patients, and this indicates the necessity for complete examination. Thirteen of these 43 patients showed major lesions such as ulcers or angiodysplasia in this last region alone. Conclusion: In-patients might require special treatment to ensure complete examination, since a considerable amount of pathologies can only be found in the ileum.